DAMPAK PEMBELAJARAN DI ERA NEW NORMAL DI MASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) - Rosmayati, Siti; Maulana, Arman (Penerbit Widina, Widina Media Utama, 2021)
Descriptive research methods are used by examining variables in naturally occurring situations through descriptions and interpretations of the conditions in which these variables are found. This research explores the impact of New Normal teaching among 101 educators in West Java, educators mostly aged 29 to 38 years, gender the largest number of female educators, in terms of teaching students for 10 years and under in state schools. The impact of New Normal teaching is expressed through challenges in resources such as very slow and/or unreliable and unstable internet connections, noisy online classrooms and lack of privacy during simultaneous online classes, lack of a licensed/registered Learning Management System (LMS). to continuously hold online classes and the lack of computers and internet connections for some teaching staff. Educators are physically ready for New Normal teaching, but educators are not emotionally ready, therefore educators prefer to teach in the classroom rather than in virtual classes. The impact on educators' adjustments is in terms of student environment, curriculum, teaching strategies, and use of technology. Age, gender, type of school and level of students taught by educators are factors that influence student teaching in the New Normal era.ABSTRAKMetode penelitian deskriptif digunakan dengan memeriksa variabel dalam situasi yang terjadi secara alami melalui deskripsi dan interpretasi kondisi di mana variabel tersebut ditemukan Penelitian ini mengeksplorasi dampak dari New Normal pengajaran di antara 101 pendidik di jawa barat, para pendidik kebanyakan berusia 29 sampai 38 tahun, jenis kelamin paling banyak tenaga pendidik perempuan, dalam hal mengajar mahasiswa selama 10 tahun ke bawah di sekolah negeri. Dampak dari pengajaran New Normal diungkapkan melalui tantangan dalam sumber daya seperti koneksi internet yang sangat lambat dan atau tidak dapat diandalkan dan tidak stabil, ruang kelas online yang bising dan kurang privasi selama kelas online secara bersamaan, kurangnya Learning Management System (LMS) berlisensi/terdaftar untuk terus menerus mengadakan kelas online dan kurangnya komputer dan koneksi internet untuk beberapa tenaga pendidik. Para pendidik secara fisik siap dalam pengajaran New Normal, tetapi tenaga pendidik tidak siap secara emosional, oleh karena itu tenaga pendidik lebih suka mengajar di ruang kelas daripada di kelas virtual. Dampak pada penyesuaian pendidik adalah dalam hal lingkungan siswa, kurikulum, strategi pengajaran, dan penggunaan teknologi. Usia, jenis kelamin, jenis sekolah dan tingkat siswa yang diajar oleh pendidik merupakan faktor-faktor yang mempengaruhi pengajaran siswa di era New Normal.